PIK3CA mutations as prognostic factor in squamous cell lung carcinoma. (January 2017) - McGowan, Marc; Hoven, Aleksandra Silye; Lund-Iversen, Marius; Solberg, Steinar; Helland, Åslaug; Hirsch, Fred R.; Brustugun, Odd Terje
Highlights: Mutation in the PIK3CA gene is frequent in squamous cell carcinomas of the lung. PIK3CA mutation was found in 11.4% of 308 tumours, most frequently in exon 20. PIK3CA mutations correlate with good prognosis in operable squamous cell lung cancer. Abstract: Objectives: Mutation in the PIK3CA gene is reported frequent in squamous cell carcinomas of the lung, but its potential prognostic role is still obscure. We have studied the prognostic importance of PIK3CA mutations as well as the relation to other markers in a large number of early stage lung cancers of squamous carcinoma subtype. Patients and methods: Tumour tissue was obtained from 308 consecutively operated lung cancer patients with squamous cell carcinoma in the period 2003–2013. DNA was isolated according to standard procedures, and mutation analysis was done with either the SnapShot method and/or using PIK3CA specific primers in the Cobas system. PD-L1-expression was analysed with immunohistochemistry After thorough follow-up (median 67.6 months), overall survival and time to relapse was calculated. Results: Tumour tissue from 102 females and 206 males were analysed. 167 (54.2%) were in stage I, 96 (31.2%) in stage II and 45 (14.6%) in stage III. PIK3CA mutation was found in 35 (11.4%) patients, most frequently in exon 20. There were no differences in sex, stage or smoking behaviour between mutated and non-mutated cases. Patients with PIK3CA mutations had a significantly longer overall survival (p = 0.042) and time to relapse (p = 0.030) than non-mutated cases, and the difference in time to relapse was also retained in stage I-cases (p = 0.044). PD-L1-expression was less frequent among mutated cases. Conclusion: Our results indicate that PIK3CA mutations may confer a survival advantage in early stage squamous cell lung cancers, but further work is needed to confirm this finding.